Analysis of the Influence of Innovative Teaching Management Mode in Universities on Students’ One-to-One Training and Psychotherapy - Wenwen Zhang (Occupational Therapy International)
Objective. This study expects to investigate and verify the intervention effect of the university’s innovative teaching management model on college students’ resilience by implementing the university’s innovative teaching management model for college students with low psychological resilience. Method. The scientific scale is used to investigate the current level of college students’ psychological resilience, and the development characteristics of college students’ psychological resilience are obtained through statistical analysis. Based on the theoretical analysis of the application of psychological resilience intervention, combined with the theory of one-to-one tutoring and operational techniques, the university’s innovative teaching management mode scheme is designed. The design adopts a quasi-experimental pre-experimental test to investigate and explore the intervention effect system of the university’s innovative teaching management mode on college students’ psychological resilience. In the intervention, each unit of activity is carried out in strict accordance with the established plan, and records and reflections are made at the end. One-to-one and face-to-face qualitative interviews were conducted with the subjects, and qualitative data were collected for qualitative analysis. Results/Discussion. Compared with the control group that did not receive the intervention, the psychological resilience of the subjects in the experimental group was significantly improved after receiving the intervention of the university’s innovative teaching management model. The university’s innovative teaching management model has a good intervention effect on the resilience of college students. The university’s innovative teaching management model scheme compiled in this study integrates a variety of psychotherapy methods and combines one-to-one psychological counseling frameworks and techniques. It is an effective and easy-to-implement intervention scheme for college students’ psychological resilience intervention.